Building partnerships in health promotion - Werkema, Danae; Dennis, Angeline; Bhatti, Priya; Vanier, Elizabeth (Electronic version published by Vancouver Island University, 2018)
Poster Poster exploring the role of student nurses in First Nations communities, and the Four Seasons Early Years Programs provided by Kw'umut Lelum Child and Family Services. https://viurrspace.ca/bitstream/handle/10613/6070/Werkemanurs313.pdf?sequence=3 Bachelor of Science in Nursing program